Sustentabilidade das comunidades de aves em duas áreas protegidas do estado de Sergipe - Aguilar, Juan Manuel Ruiz-Esparza (2014)
The destruction and modification of forested habitats in the Neotropics are a principal source of preoccupation for conservationists. Due to the fidelity to biomes or specific habitats, populations of wild birds can be used as indicators of impacts on habitat quality. Brazil is home to almost a fifth of the world s known bird species (1901 species), and also a large number of endangered species, which confers this nation with a considerable responsibility in terms of the conservation of the planet s natural resources. The present study characterizes and compares the composition and structure of the bird communities of two state conservation units (CUs) in Sergipe, as well as the knowledge of local residents with regard to this fauna, and their relationships and ecological functions, as a means of selecting indices of sustainability for the effective conservation of these populations over the long term. Data were collected in the 900-hectare Mata do Junco State Wildlife Refuge (RVSMJ), remnant of the Atlantic Forest, and the 2138 ha Grota do Angico State Natural Monument, representing the Caatinga. Data were collected in each CU using mist nets (2.5 m x 10 m), and MacKinnon lists of 10 species. A total of 129 species were recorded in each CU. In the RVSMJ, 37 species were classified as indicators of disturbed habitats (secondary forest, pastures or plantations), whereas only eight species were classified as indicators or typical of the Atlantic Forest, nine were endemic to Brazil, and two are under some risk of extinction, according to the IUCN - Herpsilochmus pectoralis (VU) and Pyriglena atra (EN). In the MNGA, 31 species were indicators of some degree of habitat disturbance, and five were specialists in decidual tropical dry forest. A single species (Herpsilochmus pectoralis) is classified as vulnerable to extinction by the IUCN, and 17 are endemic to Brazil. Local residents living in the buffer zones of the two CUs were interviewed, with the objective of documenting traditional knowledge and the use of the local fauna, with the emphasis on wild birds. Birds and mammals were cited as the principal animal found in both CUs, and in particular at RVSMJ, just over half the interviewees mentioned the titi monkey, Callicebus coimbrai. The collection of firewood, hunting, and the capture of animals for domestication were the responses that most exemplified the use of the local natural resources. The number of bird species known by local residents varied from zero to 13, and most interviewees cited fruit, seeds, and insects as food sources. The maintenance of local bird populations was seen as an important factor for the conservation of local habitats, and the control of deforestation as the principal means of protecting natural resources. These results were used to elaborate indices of sustainability based on the Pressure/State/Impact/Response approach, relating the applicability of the model to the anthropogenic impacts on the bird communities. This study intends to consolidate the management of the CUs and guarantee their conservation over the long term, providing a functional model that can be replicated in other conservation units.